Isolasi dan Karakterisasi Bakteri Endofit dari Akar Pare (Momordica charantia L.) - Mahdalena Sy. Pakaya; Julianty Akuba; Ade Ari Puspitadewi; Dizky Ramadani Putri Papeo; Andi Makkulawu (Journal Syifa Sciences and Clinical Research, 2022)
Endophytic bacteria are microbes that grow on plant tissue and can form a colony on plant tissue without producing a negative effect on the host. The endophytic bacteria have the potential to have the same activity and produce secondary metabolite as their host. The root of bitter melon (momordica charantia L.) has been known to have antibacterial activity, thus enabling the presence of endophytic bacteria, which also have antibacterial potential.This present research aims to isolate and characterize endophytic bacteria found in bitter melon (Momordica charantia L. The method used in the isolation stage is direct lanting so that the endophytic bacteria are obtained from plant tissue; macroscopic and microscopic characterization stage; inhibition test stage; inhibition test stage using disc method (Kirby-Bauer). In accordance with the results of macroscopic and microscopic characterization, the two bacteria indicate different characteristics.